2002
DOI: 10.1099/0022-1317-51-7-548
|View full text |Cite
|
Sign up to set email alerts
|

Virulence properties of Escherichia coli faecal strains isolated in Poland from healthy children and strains belonging to serogroups O18, O26, O44, O86, O126 and O127 isolated from children with diarrhoea

Abstract: Four hundred and twenty-seven Escherichia coli isolates from 427 cases of infantile diarrhoea in Poland, belonging to serogroups O18, O26, O44, O86, O126 and O127 and 150 E. coli isolates from 52 healthy children were examined for selected virulence properties. The presence of the plasmid pAA, a plasmid encoding enterohaemolysin, the genes encoding intimin (eae), bundle-forming pili (bfp), Shiga toxins I and II (stxI, stxII ) and cytotoxic necrotising factor types 1 and 2 (cnf 1, cnf 2) was investigated by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
5
33
0
Order By: Relevance
“…We confirmed that the new highly pathogenic EHEC O26:H11 clone ST29 is circulating in France and constituted most of the stx 2 -harboring EHEC O26:H11 strains studied here, as 16 of the 23 strains appeared to correspond to this clone (ST29). This finding confirms observations made by others in different countries (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the characteristics of many of the strains analyzed here differed somewhat from the characteristics described previously.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We confirmed that the new highly pathogenic EHEC O26:H11 clone ST29 is circulating in France and constituted most of the stx 2 -harboring EHEC O26:H11 strains studied here, as 16 of the 23 strains appeared to correspond to this clone (ST29). This finding confirms observations made by others in different countries (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the characteristics of many of the strains analyzed here differed somewhat from the characteristics described previously.…”
Section: Discussionsupporting
confidence: 73%
“…Until recently, EHEC O26:H11 strains isolated from humans mostly harbored Shiga toxin 1 (Stx1) (Stx1a subtype) only or, more rarely, Stx1a associated with the Stx2a subtype. In the middle 1990s, however, a new EHEC O26:H11 clone carrying the Shiga toxin Stx2a subtype alone emerged in Europe (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This new clone has also been observed in South America (19) and in the United States (1).…”
mentioning
confidence: 93%
“…Previous reports from developing countries have shown a significant association of typical EPEC strains (eae ϩ bfpA ϩ stx) with diarrhea (1,19,36). Some recent reports from developed countries have shown that atypical EPEC strains (eae ϩ bfpA) are more prevalent than typical EPEC strains (29,41). In this study, we found both typical and atypical EPEC strains significantly more often in the diarrheal group than in controls.…”
Section: Discussionsupporting
confidence: 65%
“…CNF1 is frequently produced by extraintestinal pathogenic E. coli (ExPEC) isolated from humans with urinary tract infection (De Rycke et al 1999, Russo & Johnson 2000, Boquet 2001 and occasionally detected in isolates from feces of children with diarrhea (Elliot et al 1998, Okeke et al 2000, Paciorek 2002). Production of CNF2 has been mainly found among isolates from calves with diarrhea or septicemia (Orden et al 1999, De Rycke et al 1999, Van Bost et al 2001a).…”
mentioning
confidence: 99%